BRAIN GYM BERPENGARUH TERHADAP TINGKAT AKTIVITAS DASAR SEHARI-HARI LANSIA - Novianti, Eka; Werdati, Sri; Nur Azizah, Fajriyati (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Aging process is a process of slowing down the tissue ability to repair itself or maintain its normal functions. It leads to the inability to resist infections or damages. Along with the aging process, elderly people often encounter with problems of activities of daily living and mobilization. Those problems are related to the regression of physical ability. One of the interventions to maintain physical ability and muscle strengthis movement training i.e. hands and legs movements training such as brain gym. Objective: To analyze the influence of brain gym on the level of activities of daily living in elderly at PSTW Budhi Luhur unit Bantul Yogyakarta. Methods: This study used quasy experiment method with one group pre- and post-test design. The sample was 23 elderly,employed purposive sampling technique. Data were collected before and after three times of performing brain gym and was analyzed using Wilcoxon signed rank test at a significance level of Î± = 0.05 Results: Wilcoxon signed rank test showed a significance result of -3,162, p value= 0.002 < Î± = 0.05. There was a significant influence of brain gym on the level of activities of daily living in elderly at PSTW Budhi Luhur unit Bantul Yogyakarta after 3 trainings in 3 weeks of implementation. Conclusion: There was a significant influence of brain gym on the level of activities of daily living in the elderly at PSTW Budhi Luhur unit Bantul Yogyakarta. Keywords: Brain gym, Elderly, Level of activity daily living